2022
DOI: 10.57041/pjs.v73i4.365
|View full text |Cite
|
Sign up to set email alerts
|

Combating Heat Stress in Laying Hens a Review

Abstract: Pakistan is located in the subtropical zone of the world where the ambient temperature remains higher most of the year and causes significant economic losses in commercial laying hens. The ambient temperature of some parts in Pakistan reaches up to 52 °C whilst, the ideal temperature for efficient performance for laying hens is 19-22°C. Yet, ambient temperature particularly on the higher side is very disruptive, therefore; heat stress during summer is a major problem of poultry producers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
(213 reference statements)
0
1
0
Order By: Relevance
“…This action aims to reduce stress levels in chickens, which results in reduced production and performance of laying hens. Stress regulation can be done by controlling feeding and production management (Edwards & Hemsworth, 2020;Abbas et al, 2021;Paim et al, 2021). Furthermore, another alternative strategy is that the company tries to maintain good relations with the social environment and customers (TAS 7.140).…”
Section: Quantitative Strategy Planning Matrix (Qspm)mentioning
confidence: 99%
“…This action aims to reduce stress levels in chickens, which results in reduced production and performance of laying hens. Stress regulation can be done by controlling feeding and production management (Edwards & Hemsworth, 2020;Abbas et al, 2021;Paim et al, 2021). Furthermore, another alternative strategy is that the company tries to maintain good relations with the social environment and customers (TAS 7.140).…”
Section: Quantitative Strategy Planning Matrix (Qspm)mentioning
confidence: 99%
“…The agricultural sector is one of the pillars of economic and social development for many developing and developed countries. Agriculture constitutes a major source of food, accommodates a large number of workers, provides raw materials and inputs for many industries, and obtains financial resources through export revenues [1,2]. In addition to the other commodities it provides that are used in industries, it must not be forgotten that oil is a depleting wealth that may be lost in the future, but agriculture will remain a permanent asset for the livelihood of future generations, and developing the agricultural sector is one of the most important issues that the world seeks to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…AgeThe results of the research showed that the minimum age of the respondents was (22) years, and the oldest age was (62) years, with an average age of (45). The age of the educators was divided into three categories using the range law, as shown in Table(2): Distribution of age groups of educators.…”
mentioning
confidence: 99%
“…Therefore, the increasing environmental temperature during the summer and amid global warming is an apparent concern of the poultry industry, leading to heat stress and severe economic loss ( Wasti et al, 2020 ). To combat the harmful impact of heat stress on chickens, various nutritional, managemental, and genetic strategies have been implemented ( Saeed et al, 2019 ; Abbas et al, 2022 ). Mitigating heat stress using managemental and genetic strategies is expensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%